The Impact of Frame Running on Quality of Life in Young Athletes With Mobility Limitations - van Schie, Petra E. M.; van Eck, Mirjam; Bonouvrié, Laura A.; Edelman Bos, Arnoud M. M.; Buizer, Annemieke I. (Frontiers in Sports and Active Living, 2022)
Purpose: The para-athletic sport Frame Running is developed for persons with neurological impairments causing severe impairment limitations of walking ability. Participating in sports can contribute to a better quality of life (QoL). It is unknown if participation in Frame Running contributes to QoL in children with mobility impairmentslimitations. This study aims to explore the changes in QoL in children and youth who started Frame Running. Material and Methods: We conducted a cross-sectional study amongst young Frame Running athletes with mobility impairments limitations due to various underlying causes, aged 6 to 19 years, who are members of one of the Frame Running groups in the Netherlands. For 62 athletes, parents completed the Psychosocial Impact of Assistive Devices Scale (PIADS) questionnaire (subscales: competence, adaptability and self-esteem). For six athletes, parents were interviewed to obtain more in-depth insight in the perceived changes in the QoL of their children. Results: Parents (of 58% boys, mean age 12yr4mo; SD 3yr3mo; 52% supported walkers) reported a significant positive change on all three subscales of the PIADS questionnaire since their children started Frame Running. Most change was experienced in the items performance, the ability to participate, happiness and self-confidence. Quotes of the parents who were interviewed elucidated these changes. Conclusion: Frame Running increased QoL in young athletes with a mobility impairmentlimitation. Frame Running may therefore be advised for these children and youth to improve QoL.